Erasing the Line between Students and Instructors: The Influence of Classrooms and Online Learning Spaces on Student Engagement - Caroline S. Parsons (Journal of the Scholarship of Teaching and Learning)
This study investigated the influence of physical and virtual learning spaces on student engagement in a modern university setting. Qualitative analysis of an active learning classroom that employed the use of roundtables was conducted. Interview and focus group data from students and faculty, along with classroom observations, resulted in the finding that the circular arrangement of this active learning classroom positively influenced student engagement by promoting immediate exchange of feedback, agency, and a system of accountability. This study also resulted in the finding that virtual learning spaces influence student engagement and the amount of engagement is heavily moderated by instructor efforts to facilitate interpersonal immediacy. Both physical and virtual learning spaces influenced student engagement and the level of engagement was heavily moderated by students’ desire for engagement. Recommendations and suggestions for future research are provided.